Belts and chains - FOS (John Deere, 1993)
This book explains belt and chain drives so that the reader can understand and service them with speed and skill. The belt must be design, manufactured and maintained properly to enable the belt to transfer this torque efficiently and reliebly. It should also be designed to slip or break if the upper torque limits are exceeded in order to prevent possible damage to other components. Chain drives are a form of flexible gearing. The chain is like an endless gear rack, while the sprokets are similar to pinions or driven gears.